Assessment of heavy metals in the fish mormyrus deliciousus and heterobranchus longifilis from alaro Stream in Ibadan, Nigeria (2014)
study was carried out on the assessment of heavy and trace metals in the tissues of two fish species, Mormyrus deliciousus and Heterobranchus longifilis in Alaro stream ecosystem in Ibadan, Nigeria. Cast nets with mesh sizes ranging between 30- 50 mm with varying dimensional sizes were used for catching the two fish species over 3-month duration. Sixty-seven fishes were caught in the sampling with M. deliciousus making up 27 of the total while H. longifilis was 40 over 3-month duration. Fish dissections (M. deliciousus: n=27; H. longifilis:n=40) were carried out using dissecting set to remove the gills, gut, liver, fins and muscle which were oven dried at 1050C for 6 hours. Pulverized tissues and organs were acid-digested for heavy and trace metal analyses using the inductively coupled plasma-mass spectrometer (ICP-MS). Percentage recoveries from the reference material were all above 70% with a range of 75. 25% (Pb) to 104. 54% (Ag). Mean of some heavy and trace metals were comparatively higher in M. deliciousus: Mg(10082ppm, fins), Co(8. 56ppm, muscle), Cu(175. 78ppm, liver), Zn(275. 2ppm, muscle), As(0. 963ppm, muscle), Se(11. 80ppm, liver), Mo(1. 73ppm, liver) and Pb(14. 12ppm, liver) while Na(12980ppm, bone), K(30912ppm, liver), Ca(203189ppm, bone), V(12. 98ppm, liver), Mn(752. 9ppm, liver), Fe(10092. 0ppm, liver), Cd(3. 208ppm, liver) were higher in H. longifilis whereas the following trace metals were the same for both species of fish: Nickel, Ni (5. 82ppm) and Silver, Ag (2. 33ppm). Most of the heavy metals were high due to their physiological requirement in the tissues of the fish species. As, Ag, Cd and Pb exceeded the recommended limits set by the World Health Organization for most of the tissues and organs in M. deliciousus and H. longifilis. This shows that these fish species caught in Alaro stream ecosystem are not safe for human consumption